Secret Seven Mystery - Blyton, Enid (London Hodder Children's Books, 2004)
A girl runs away from home - and it's up to the Seven to find her! Jack's little sister Susie is up to her usual tricks - but she can't put the Seven off the trail of clues! Can they track down Elizabeth, and discover who stole the money from her school?
Keywords: Children's Literature - Fiction : Adventure